Tropical forest-transition landscapes: a portfolio for studying people, tree crops and agro-ecological change in context - Dewi, Sonya; Noordwijk, Meine van; Zulkarnain, Muhammad Thoha; Dwiputra, Adrian; Hyman, Glenn G.; Prabhu, Ravi; Gitz, Vincent; Nasi, Robert (Informa UK Limited, 2017)
Nudging the development trajectory of tropical landscapes towards sustainability requires a global commitment and policies that take diverse contexts and forest transitions into account. Out-scaling and upscaling landscape-level actions to achieve sustainable development goals globally need to be based on understanding of extrapolation domains and interconnectivity of products and services. We evaluated three portfolios of tropical landscape observatories and quantified extrapolation domains across ecological zones, stages of forest transition, human development index (HDI), population density and potential prominence of four dominant tropical tree crops (arabica coffee, cacao, rubber and oil palm). The ASB Partnership for Tropical Forest Margins portfolio was focussed on active humid forest margins and the Poverty and Environment Network on early stages of forest transition. The portfolio of sentinel landscapes of the Forests, Trees and Agroforestry (FTA) research programme provides a 5% sample of pantropical area, 8% of people, 9% of tree cover and 10–12% of potential tree crop presence, with quantified biases across zones, transition stages and HDI. In the ‘water tower’ configuration, relatively high population density coincides with biodiversity, coffee expansion and contested ecosystem services. The extrapolation domain of the FTA portfolio includes trade-off (tree loss) and synergy (restoration) phases of tropical forest transition.